2005
DOI: 10.1007/bf02708743
|View full text |Cite
|
Sign up to set email alerts
|

Immunoexpression of p53, Ki-67 and E-cadherin in basaloid squamous cell carcinoma of the larynx

Abstract: BSCCL is an aggressive variant of the squamous cell carcinoma and has a high expression of p53 and Ki-67 with a low expression of Ecadherin. These results could be related to the aggressiveness of the disease and its poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…Some authors have recently reported the value of p53, Ki-67 and e-cadherin [39], p27 Kip1 [40], and apoptosis inhibitor protein [41] as independent predictors of prognosis in BSCCs, but these findings need further confirmation in large series and its acceptance and use in daily practice.…”
Section: Discussionmentioning
confidence: 93%
“…Some authors have recently reported the value of p53, Ki-67 and e-cadherin [39], p27 Kip1 [40], and apoptosis inhibitor protein [41] as independent predictors of prognosis in BSCCs, but these findings need further confirmation in large series and its acceptance and use in daily practice.…”
Section: Discussionmentioning
confidence: 93%
“…Eleven of these studies suggest that patients with BSCC have a worse prognosis, 1,2,10,11,13,15,18,20,[24][25][26] whereas the remaining studies either suggest that the behavior of BSCC is not different from SCC, 5,12,14,16,17,[21][22][23]27,28 or did not address the issue of comparative prognosis. 19,29 The common factor suggesting that BSCC has a worse prognosis in these studies has been the pro- pensity for BSCC to present in advanced stages and to have higher rates of hematogenous spread. In our case-control study, only patients who had lymph node involvement were included.…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting the difficulties in selecting the best treatment for BSCC, biologic molecular patterns may provide some clues. Promising cell cycle markers, 14,29,33,34 apoptosis, differentiation, stem cells, and loss of heterozygosity 35 may provide directions for better treatment selection in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…This view has been questioned in recent articles which note these conclusions are based largely on limited numbers of case reports [22][23][24]. Several genetic mechanisms have been proposed for this assumed aggressive behavior, including cell-cycle regulators [25], increased tumor angiogenesis [26], and tumor suppressors and lack of apoptosis [9,13,14,27], with variable results, and precise genetic mechanisms for more aggressive behavior remain elusive. In addition to examining proliferation markers c-kit, MIB-1 and p63, we sought a connection with human papilloma virus (HPV) using p16 staining.…”
Section: Introductionmentioning
confidence: 92%